Disparities in telehealth utilization in patients with pain during COVID-19. (14th May 2022) - Mueller, Bridget R.; Lawrence, Steven; Benn, Emma; Nirenberg, Sharon; Kummer, Benjamin; Jette, Nathalie; George, Mary-Catherine; Robinson-Papp, Jessica
Abstract : Supplemental Digital Content is Available in the Text. For patients living with pain in New York City during the first wave of COVID-19, the relationship between sociodemographic factors and telehealth utilization evolved with time. Abstract : Introduction: The shift from in-person visits to telehealth visits during the COVID-19 pandemic presented unique challenges for patients with pain. Disparities in health care access already existed, and the impact of telehealth on these inequities has not been studied. Objectives: To identify sociodemographic characteristics of patients with pain obtaining care through video, telephone, and in-person visits as social distancing restrictions evolved during the COVID-19 pandemic. Methods: Using our institutional clinical data warehouse, we identified 3314 patients with pain receiving care at a large academic institution in New York City during a baseline period (September 23, 2019–March 22, 2020) and counted telephone, video, and in-person visits during the following conditions: a shutdown period (March 23, 2020–May 23, 2020), when nonessential in-person visits were strictly limited, and a reopening period (May 23, 2020–September 23, 2020), when restrictions were relaxed and in-person visits were available. Patients were categorized into 4 groups based on the technology used to complete a visit: (1) video, (2) telephone, (3) in-person, and (4) no visit. Results: Patients who were older, publicly insured, and identified as Black or Hispanic were overrepresented in the telephone visit group during shutdown and the in-person group during reopening. A video visit during shutdown increased the likelihood of continued video visit use during reopening despite the return of in-person visits. Conclusions: Results show differences in how patients with pain accessed clinical care in a socially distanced world and that flexibility in method of health care delivery may reduce barriers to access. Future research will identify factors (eg, Internet access, digital literacy, provider–patient relationships) driving heterogeneity in telehealth use in patients with pain.